Criteria for the formation of sediment plugs in alluvial rivers - Boroughs, Craig B., author; Abt, Steven R., advisor; Thornton, Christopher I., committee member; Julien, Pierre Y., committee member; Watson, Chester C., committee member; Anthony, Deborah J., committee member (Colorado State University. Libraries, 2005)
There are several documented cases of sediment plug development in alluvial rivers. General qualitative theories have been offered about the cause of plug formation that pertain to such factors as a sudden decline in sediment transport capacity, the effect of debris in a channel, or human factors such as watershed management. These findings are pertinent but do not contribute to the understanding of the specific processes occurring at the location where plugs develop. Site characteristics, processes, and associated parameters regarding sediment plug formation were evaluated based on a comprehensive literature review, evaluation of data, and discussions with other researchers. All of these topics were analyzed for a focus study reach along the Middle Rio Grande in New Mexico to identify consistencies between periods when plugs formed versus periods when plugs did not develop. The topics were also analyzed against information from other river systems where plugs developed. A theory was formulated regarding the cause of plug development. Sediment plugs always occurred in alluvial rivers at the location of a constriction that abruptly forces a significant portion of flow overbank. As flows are lost, sediment transport capacity decreases, but the total sediment load in the main channel does not reduce by the same proportion. As a result, deposition ensues in the main channel. If flows continue to overbank for weeks, the deposition will eventually completely clog the main channel of the river. This theory was tested using a calibrated and validated original sediment transport/movable bed computer model. Criteria for plug formation were developed with the model and tested against a case for plug development and against another scenario when a plug did not form. These criteria can be used to identify critical thresholds for plug development. The level of plug formation (55% of the main channel, 70% of the main channel, etc.) can be determined to a specified level of confidence. River managers not only have a better understanding as to why plugs form in alluvial rivers but will be able to apply these criteria to evaluate scenarios for a site that is prone to plug formation and address the conditions that might lead to plug development.
Keywords: civil engineering; hydrology; hydrologic sciences